Implied volatility and the cross section of stock returns in the UK - Poshakwale, Sunil S.; Chandorkar, Pankaj Avinash; Agarwal, Vineet (Elsevier, 2019)
The paper examines the relationship and the cross-sectional asset pricing implications of risk arising from the innovations in the short and the long-term implied market volatility on excess returns of the FTSE100 and the FTSE250 indices and the 25 value-weighted Fama-French style portfolios in the UK. Findings suggest that after controlling for valuation, macroeconomic, leading economic and business cycle indicators, returns exhibit a strong negative relationship with the innovations in both the short and the long-term implied market volatility. The cross-sectional regression provides new evidence that changes in both short and long-term implied market volatility are significant asset pricing factors with negative prices of risk, which suggests that (i) investors care about ex-ante volatility and (ii) they are willing to pay for insurance for future uncertainty.
Keywords: VFTSE; Excess Returns; Asset Pricing; Business Cycle; ICAPM; implied volatility